Digital health technologies for universal health coverage: a promising change - Kodali, Prakash Babu; Das, Shankar (Current science (Bangalore), 2021)
Digital health technologies act as health system strengthening tools and facilitate achievement of universal health coverage (UHC). In line with the United Nations sustainable Development Goals, India launched the Ayushman Bharat Programme (ABP) to strengthen health services and achieve UHC. Digital health technologies could be instrumental in improving the efficiency of ABP. Given that India is in the initial steps towards UHC and digital health deployment, synergy between health programmes and digital health policies is essential to realize the goal of UHC. This article aims to discuss the scope of digital health technologies for achieving UHC, their application, opportunities and challenges in the context of ABP in India.